Prospective use of bloom filter and muxing for information centric network caching - Abdullahi, Ibrahim; Hassan, Suhaidi; Arif, Suki (Asian Research Publishing Network (ARPN), 2015)
Information dissemination as the main objective of setting up the Internet has seen different folds to improve its course.Information centric networking (ICN) has been introduced with the aim of curtailing some future challenges posed at the traditional Internet in the nearest future.ICN advantage of caching chunks of information on-path and off-path of the network stands the paradigm out as an alternative shift from host centric network to name centric.ICN caching approach can thereby significantly reduce amount of times a host is visited.Bloom Filter with its advantage of fast searching and false positivity characteristics are seen as form of message retrieval practice to improve interest serving on the network.This paper analyzed the advantages of vending and adopting Bloom Filters and Muxing as research directions to minimize excessive bandwidth consumption, lesser delays, prompt delivery of information, higher throughput and the ability to share information from troubled stations.Concepts are proposed and wider algorithms are pointed out to increase the overall ICN framework as related to caching and other network services.